An Efficient Numerical Model for Immiscible Two-Phase Flow in Fractured Karst Reservoirs (Communications in Computational Physics, 2018)
Numerical simulation of two-phase flow in fractured karst reservoirs is stilla challenging issue. The triple-porosity model is the major approach up to now. However, the triple-continuum assumption in this model is unacceptable for many cases.In the present work, an efficient numerical model has been developed for immiscibletwo-phase flow in fractured karst reservoirs based on the idea of equivalent continuumrepresentation. First, based on the discrete fracture-vug model and homogenizationtheory, the effective absolute permeability tensors for each grid blocks are calculated.And then an analytical procedure to obtain a pseudo relative permeability curves for agrid block containing fractures and cavities has been successfully implemented. Next,a full-tensor simulator has been designed based on a hybrid numerical method (combining mixed finite element method and finite volume method). A simple fracture system has been used to demonstrate the validity of our method. At last, we have usedthe fracture and cavity statistics data from TAHE outcrops in west China, effective permeability values and other parameters from our code, and an equivalent continuumsimulator to calculate the water flooding profiles for more realistic systems.